Emergence of highly resistant Candida auris in the United Arab Emirates: a retrospective analysis of evolving national trends - Thomsen, Jens; Abdulrazzaq, Najiba M.; Oulhaj, Abderrahim; Nyasulu, Peter S.; Alatoom, Adnan; Denning, David W.; Al Dhaheri, Fatima; , the UAE AMR Surveillance Consortium; Menezes, Godfred Antony; Moubareck, Carole Ayoub; Senok, Abiola; Everett, Dean B. (Frontiers in Public Health, 2024)
The Centers for Disease Control lists Candida auris, given its global emergence, multidrug resistance, high mortality, and persistent transmissions in health care settings as one of five urgent threats. As a new threat, the need for surveillance of C. auris is critical. This is particularly important for a cosmopolitan setting and global hub such as the United Arab Emirates (UAE) where continued introduction and emergence of resistant variant strains is a major concern.The United Arab Emirates has carried out a twelve-years of Antimicrobial resistance surveillance (2010-2021) across the country, spanning all seven Emirates. A retrospective analysis of C. auris emergence from 2018-2021 was undertaken, utilising the demographic and microbiological data collected via a unified WHONET platform for AMR surveillance. . Results: 908 non-duplicate C. auris isolates were reported from 2018-2021. An exponential upward trend of cases was found. Most isolates were isolated from urine, blood, skin and soft tissue, and the respiratory tract UAE nationals comprised 29% (n=186 of 632) of all patients; the remainder were from 34 other nations. Almost all isolates were from inpatient settings (97%, n=809). The cases show widespread distribution across all reporting sites in the country. C. auris resistance levels remained consistently high across all classes of antifungals used. C. auris in this population remains highly resistant to azoles (fluconazole, 72.6% 2021) and This is a provisional file, not the final typeset article amphotericin. Echinocandin resistance has now emerged and is increasing annually. There was no statistically significant difference in mortality between Candida auris and Candida spp. (non-auris) patients (p-value: 0.8179), however Candida auris had higher ICU admission rate (p-value < 0.0001) and longer hospital stay (p<0.0001) compared to Candida spp. (non-auris) patients.The increasing trend of C. auris detection and associated multidrug resistance phenotypes in the UAE is alarming. Continued C. auris circulation in hospitals requires enhanced infection control measures to prevent continued dissemination.